Sistem Informasi Inventaris Berbasis Qr-Code Dengan Metode Rapid Application Development - Kelvin Kelvin; Rahayu Amalia (Journal of Information System Research (JOSH), 2022)
The Inventory System is an integrated inventory management information system for all agencies in order to carry out the administration of management and data collection of goods. In this case, making an Inventory system that will make work easier, as well as recording the inventory owned by the Candradimuka High School company. Because the process of recording inventory and managing Inventory data is still in the conventional way where the data for each existing Inventory is recorded and recorded in a ledger, this often causes problems, such as errors in finding the Inventory file, Inventory being confused in numbering and. The solution that needs to be done is to build a web-based Inventory information system with the PHP programming language to manage and collect data on Inventory, the system is also supported by the QR-Code feature. this feature itself is a code that can be read by a computer using QR-Code technology to help the process of searching and checking data automatically. The methodology used in developing this system using QR-Code is Rapid Application Development or often known as the RAD method, this method is often used by application developers in developing an information system. This method aims to develop applications quickly through repetition and repeated feedback. The result that will be obtained is a system that can collect inventory data and generate inventory reports with the help of a QR-Code.